THE IMPACT OF FOREIGN TRADE IN AGRICULTURAL PRODUCTS OF BOSNIA AND HERZEGOVINA WITHIN THE FRAMEWORK OF CEFTA 2006 - Ćejvanović, Ferhat; Ivanković, Marko; Lasić, Marija; Vaško, Željko (Economics of Agriculture, 2014)
In modern conditions, characterized by the growing importance of foreign trade between the countries, relations of a country with international environment play an increasingly important role in economic development. Over the last decade the process of economic integration through the removal of barriers for the free movement of goods, services, money and people has improved job creation and economic growth. From economic cooperation with foreign countries should expect positive effects on the economy of the state if the external economic factor used in accordance with the plans and programs of economic development of a country. Thereto, there are social forces that can decide relatively independently to all elements of internal development and cooperation with foreign countries. The objective of this study was to investigate the effect of the CEFTA 2006 on the foreign trade of agricultural products in Bosnia and Herzegovina. In this respect it may be noted that foreign trade of agricultural products has an impact on the agricultural sector in Bosnia and Herzegovina.